Performance and reduction of carbon footprint for a sustainable campus - Lim, M. (2020)
Thisresearch is to analyze and reduce the emission of carbon footprint around campus in order to build a sustainable campus for future generations. One of the most profound issue faced by the world today is the rise of temperature which is also known as global warming. The emission of GHGs has been an alarming issue in our world today which causes not only the rise of temperature but also disastrous natural disasters such as flood, hurricane, drought and many more. Like other developing countries, Malaysia have given its full support and cooperation in its attempt to achieve a sustainable development. In Malaysia, there are several policies and legislation developed to encourage sustainability in four major areas which are water and waste management, transportation, energy and building. The importance of higher education institutions such as universities should address the diverse needs of local societies and promote sustainability. Universities should also consider including sustainability into student’s education and program to promote the environmental issues which have been one of the highest concerns around the world. Therefore, the focus of this research is to analyze and reduce the carbon footprint for a sustainable campus. Hence, the aim of this research is to analyze the emission of carbon footprint throughout the campus such as traveling to class and to suggest alternatives that the student or staff can take in order to reduce the emission of carbon footprint around campus and to build a sustainable campus. © BEIESP.